ANCAMAN TERHADAP DEMOKRATISASI DESA DI BALIK PERPANJANGAN MASA JABATAN KEPALA DESA - Umbu Pariangu; La Ode Muhammad Elwan (Halu Oleo University, 2023)
The extension of the village head's term of office from 6 years to 9 years as a result of the revision of Law Number 6 of 2014 concerning Villages in Article 39, cannot be separated from the influence of compromises or political transaction relations between politicians in the DPR and village heads related to the 2024 Election. this is to analyze the decision to extend the term of office of the village head, beyond simply articulating the normative wishes of the village heads, namely as a threat to village democratization. The study method is qualitative, through literature studies, explored using data and information sources related to the extension of the position of the village head through the ratification of the revision of Law No. 6 of 2014 concerning Villages in the context of electoral interests in the 2024 elections and threats to village democratization. Then the data is classified and analyzed. The results of the study concluded that the extension of the village head's term of office to 9 years has the potential to threaten village democratization because it has implications for the tendency to abuse power, one of which is with village funds as the object, there is a saturation of the political psychology of the community, and the circulation of village leadership is jammed due to the increasing narrowing of the people's political evaluation space against the village head.